Biology Crocidolomia pavonana Fabricus (Lepidoptera: Pyralidae) Rearing With Artficial Diets in a Laboratory - ILHAM, NURHADI (Jurnal Sains Pertanian Equator, 2019)
Crocidolomia pavonana (F) is one of the Olygophagic pest and is the main pest in family plants (Brassicaceae) which can result in yield loss of up to 65.8% .This study aims to determine the development and reproduction of C. pavonana (F) which is maintained with artificial diets in the laboratory. The Research was carried out in the Tanjungpura University Faculty of Agriculture Plant Pest Laboratory which began from October to January. C. pavonana (F) is preserved in a 50 ml plastic cups.The artificial diets made from Phaseolus vulgaris L. with the addition of other supporting ingredients according to the Salama method (1970).Then do the multiplication of test insects until they reach F2. Furthermore, cohort observations were carried out using 100 individual 1 instars per glass. The parameters observed were life cycle, mortality, sex ratio, fecundity, and egg fertility.The observations were made using 100 instars 1 as individual cohorts per glass .The results showed the development period of C. pavonana (F) from hatching to adult ranged between 24 "“ 30 days, C. pavonana (F) life cycle from egg to produce eggs again lasts 28 - 33 days an average of 30.57 days, the age of eggs until dead individual lasts 8-52 days an average of 39.23 days, the egg stage ranged from 3-5 days an average of 4 days. Larvae consist of 4 instars, first instar stage duration (3-5 days) an average of 4.04 days, second instar (3-5 days) an average of 3.08 days, instar III (2-5 days) an average of 2.82 days, IV instar (2-3 days) an average of 2.08 days, pre-pupa (2-3 days) an average of 2.42 days and pupa (7-9 days) an average of 8.26 days. The length of life of male adult ranges between 2 "“ 29 days an average of 15.90 days and female adult between 4- 27 days an average of 12.90 days. The pre-laying period ranges from 2- 5 days an average of 3.3 days and the post-nesting period ranges from 2 - 11 days an average of 4.95 days.Egg fertility with an average of 88.23%. The average number of eggs produced is 229.85. Keywords : Artificial Diets, Biology, C. pavonana (F), Phaseolus vulgaris L.